Examining the Impact of Intermediate Cooling on Mechanical Properties of 22MnB5 in a Tailored Tempering Process † - Reihani, Alborz; Heibel, Sebastian; Schweiker, Thomas; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2024)
Tailoring the properties of hot-stamped components offers the potential to enhance crash performance while simultaneously improving downstream joining processes. In recent years, an innovative technology suited for achieving tailored properties involving the utilization of a specialized furnace chamber, known as the TemperBox®, has been introduced. Within this chamber, a cooled aluminum mask shields specific areas of the blank from incoming heat radiation and concurrently absorbs the blank’s own radiation. The duration of the heat radiation exchange can influence the diffusion-dependent phase transformation and, consequently, the resulting mechanical properties. Hence, the intermediate cooling duration assumes a pivotal role as a parameter, as is investigated in this study. To examine the effects, specimens of the steel 22MnB5 AS150 are subjected to intermediate cooling of varying durations, followed by forming and partial quenching. The temperature profile of the blank during intermediate cooling prior to forming and quenching is analyzed. Subsequently, the tailored hot-stamped components are assessed for hardness, strength, ductility, and thickness strain. The study reveals that with increasing duration of partial intermediate cooling and targeted radiation exchange, a homogeneous ferritic–pearlitic structure is formed from an austenitic structure. This uniform structure of ferrite and pearlite is reflected in lower hardness and strength values, along with improved ductility. Additionally, this paper introduces a simulation methodology designed to calculate the dynamics of thermal radiation and the kinetics of phase transformation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: heat exchange; heat radiation dynamics; hot stamping; simulation; tailored tempering; view factor